Newari Heritage, Commoner To Luxury - A State To Loss Identity - A Case Of Kathmandu - Shrestha, Sakar (MAJ - Malaysia Architectural Journal, 2025)
Newari Architecture is the vernacular architecture of the indigenous people of the Kathmandu Valley which were at the top of its golden years of civilization with its’ culture, business, and the most importantly Architecture Heritage during the period of Malla Dynasty of Kathmandu Valley came to rule at 1200 AD. After the horrific earthquake of April 25th 2015 in Nepal, It has never been more challenging to have a change in people’s mind and especially in architects role in recognizing and working on the preservation, restoration of vernacular architecture of Nepal which shall be headed to the direction in restoring and making the Kathmandu Valley a “Heritage Capital of Nepal”. Paper will focus on how the ever changing pace of architecture trend related to many factors which are not only overtaking but has led to the diminishing of the rich heritage which once was the prominent factor of Vernacular Sustainability and Kathmandu Valley’s Architectural Cultural Heritage Sustainability. We shall not forget that only some certain palaces, buildings, or temples be the part of tagged heritage but every magnificent details of the arts and its senses whether be on the crafts of façade’s exposed bricks, windows, doors adds the beauty and makes the heritage great and actually gives the liveliness soul to the heritage.